1939
DOI: 10.1098/rspa.1939.0103
|View full text |Cite
|
Sign up to set email alerts
|

The friction of clean metals and the influence of adsorbed gases. The temperature coefficient of friction

Abstract: Experiments on electron diffraction and electron emission, as well as optical and other methods, have made it abundantly clear that, when a solid is cleaned in air by any ordinary method, its surface is still covered by a film of oxide, water vapour, and other adsorbed impurities. The surface film is often several molecular layers in thickness. Any complete theory of friction must take this film into consideration. Most experiments on the friction of metals are not made with metallic surfaces a t all, but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1959
1959
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Bowden and Young studied the friction of a platinum wire on a platinum cylinder subject to electrical potential in dilute sulphuric acid [50]. They found high friction at intermediate potentials and lower friction at negative and high potentials and, based on previous work on the influence of gases on the friction of clean metals [113], they proposed that the reduced friction regions corresponded to the formation of monolayers of hydrogen and oxygen, respectively. However there appears to be no direct evidence of such monolayers and the authors also proposed a parallel mechanism based on electrical double layer repulsion as outlined below.…”
Section: H 2 or O 2 Releasementioning
confidence: 99%
“…Bowden and Young studied the friction of a platinum wire on a platinum cylinder subject to electrical potential in dilute sulphuric acid [50]. They found high friction at intermediate potentials and lower friction at negative and high potentials and, based on previous work on the influence of gases on the friction of clean metals [113], they proposed that the reduced friction regions corresponded to the formation of monolayers of hydrogen and oxygen, respectively. However there appears to be no direct evidence of such monolayers and the authors also proposed a parallel mechanism based on electrical double layer repulsion as outlined below.…”
Section: H 2 or O 2 Releasementioning
confidence: 99%
“…There are also other reaction products in oil and gas phases, which offer important insights into surface reactions. Bowden and Hughes have reported that a small but finite amount of gas evolved from a tribological contact when a cylinder was slipped on a metal wire under vacuum; however, at the time of this study the components of the evolved gas could not be analyzed. Now, changes in gaseous components from adsorption and surface reactions can be detected by a quadrupole mass spectrometer.…”
Section: Introductionmentioning
confidence: 88%